Synonymy in English and Bulgarian Military Terminology: (a contrastive study) - Georgieva, Valentina (Armenian Folia Anglistika, 2013)
The article discusses and investigates various expressions of synonymy in terms related to the maintenance of peace in English and Bulgarian. Detailed investigation based on factual data indicates that despite the tendency towards standardization and uniformity, the military vocabulary in English and Bulgarian is expressed by various and numerous types of synonymy.